Gandhism and Indian English fiction : the Sword and the sickle, Kanthapura, and Waiting for the Mahatma - Patil, V. T. (Devika Publications, 1997)
Study of three novels of Mulk Raj Ananad, Raja Rao, and R.K. Narayan.